WIsH: who is the host? Predicting prokaryotic hosts from metagenomic phage contigs - Galiez, Clovis; Siebert, Matthias; Enault, François; Vincent, Jonathan; Söding, Johannes (Bioinformatics (Oxford, England), 2017)
WIsH predicts prokaryotic hosts of phages from their genomic sequences. It achieves 63% mean accuracy when predicting the host genus among 20 genera for 3 kbp-long phage contigs. Over the best current tool, WisH shows much improved accuracy on phage sequences of a few kbp length and runs hundreds of times faster, making it suited for metagenomics studies. OpenMP-parallelized GPL-licensed C ++ code available at https://github.com/soedinglab/wish. clovis.galiez@mpibpc.mpg.de or soeding@mpibpc.mpg.de. Supplementary data are available at Bioinformatics online.